Treatment of Femoral Shaft Fractures in Children Less than 5 Years of Age: A Study Comparing the Single Leg Spica with the Traditional Spica (Journal of Pakistan Orthopaedic Association, 2024)
Objective: Femoral shaft fractures in paediatric patients pose significant challenges in management, with various treatment options available. Single-leg spica casting has emerged as a potential alternative to traditional spica casting, aiming to reduce family burden and material usage while maintaining clinical efficacy.Methods: We conducted a prospective study involving 72 paediatric patients aged 1 to 5 years diagnosed with low-velocity femoral shaft fractures. Exclusion criteria encompassed high-energy fractures, open fractures, extension of fracture into metaphysis or physis, pathological fractures, simultaneous fractures involving the ipsilateral or contralateral leg, skeletal disorders, suspicion of child abuse, and developmental delay. Spica casting was employed as the treatment modality, with patients randomly assigned to receive single-leg walking spica casting or traditional spica casting based on surgeon experience. Clinical outcomes were assessed using trauma history, physical examination, radiographs, and the Impact on Family Scale. Data were analysed using IBM SPSS version 24, employing descriptive statistics and the Student's t-test for group comparisons.Results: Single-leg spica casting significantly reduced family burden compared to traditional spica casting (p < 0.05). However, both methods demonstrated similar clinical outcomes in terms of hospital stay, time to callus formation, and time to union. The single-leg spica group required more wedge adjustments (16.67% vs. 5.56%, p < 0.05). Skin problems were slightly more prevalent in the traditional spica group at the time of cast removal, but all patients recovered uneventfully.Conclusion: Our study supports the use of single-leg spica casting as an effective alternative in managing low-energy femoral shaft fractures in paediatric patients aged 1 to 5 years. The findings highlight the potential benefits of single-leg spica casting in reducing family burden and material usage while maintaining comparable clinical outcomes.